Vitex trifolia: AN ETHNOBOTANICAL AND PHARMACOLOGICAL REVIEW - M, Suchitra; VARGHESE CHERIYAN, BINOY (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The perspective of this review is the list of activities carried out or studied along with description, habitat macro-microscopy, phytoconstituents, medicinal uses, clinical studies, and toxicology on the plant Vitex trifolia. Methods: A large number of the species of the Genus Vitex are widely employed in Indian traditional systems of medicine. A total of 270 plant species of genus Vitex have been identified worldwide. V. trifolia is used in Ayurveda and Unani. These species are rich source of secondary metabolites such as polyphenolic compounds, terpenoids, phytosterols, protein and amino acids, tannins, and saponins. Results: The results of various studies V. trifolia possess larvicidal, analgesic, anti-inflammatory, antimicrobial, antioxidant, hepatoprotective, antihistaminic, and antiasthmatic properties. Conclusion: The review on V. trifolia explains that there is a need for detailed study on its clinical relevance and safety of plant extracts.